Timing and durability of response to erenumab in patients with episodic migraine - McAllister, Peter J.; Turner, Ira; Reuter, Uwe; Wang, Andrea; Scanlon, James; Klatt, Jan; Chou, Denise E.; Paiva da Silva Lima, Gabriel (Headache, 2021)
Objective We sought to evaluate temporal response patterns to erenumab treatment in patients with episodic migraine. Background Although many patients treated with erenumab experience onset of efficacy as early as 1 week, clinical benefits of migraine preventive therapies may accrue with continued treatment. Furthermore, details about the maintenance of clinical responses have not been reported. Methods This was a post hoc analysis of a 6‐month, randomized, double‐blind, placebo‐controlled, phase 3 study of erenumab for the prevention of episodic migraine. We analyzed temporal responses to erenumab using a threshold of ≥50% reduction from baseline in monthly migraine days (MMDs). Results During the 6‐month treatment period, 73.7% (230/312) and 79.6% (253/318) of patients in the erenumab 70 mg (n = 312) and 140 mg (n = 318) groups, respectively, achieved a response in at least 1 month. In this group of responders, at least half reached first monthly response (first month with ≥50% reduction from baseline in MMDs) by month 2 and at least 75% of them by month 3. The remainder responded in months 4–6. Of patients in the erenumab 70 and 140 mg groups, 35.3% (110/312) and 41.8% (133/318), respectively, responded over months 1–3 (mean response over first 3 months). Of these patients, 81.8% (90/110) and 81.9% (109/133) maintained this response over months 4–6 (mean response over last 3 months) in the 70 and 140 mg groups, respectively. Many patients who did not achieve an initial response (≥50% reduction from baseline in MMDs during month 1) responded later with continued treatment, with approximately one‐half or more of initial nonresponders responding by months 4–6. Conclusions These results support guidelines recommending at least 3 months following the initiation of erenumab for migraine prevention before the assessment of response.